HAK DAN KEWAJIBAN ISTRI TERHADAP SUAMI VERSI KITAB `UQÛD AL-LUJJAIN - Iim Fahimah; Rara Aditya (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
When women get higher education, divorce is more prevalent. This is a problem that must be resolved. Students at Islamic boarding schools are known for their obedience to their husbands compared to those who do not study at Islamic boarding schools. The assumption is because there is an influence from family coaching education in the book `Uqûd al-Lujjain fi bayani huquqi zaujain which is taught in the pesantren. The focus of the study is how the substance and moral message about the rights and obligations of husband and wife contained in the book so that it can equip muslim women as wives in fostering families well. This research is a library research with descriptive-analytical method with a normative-philosophical approach. The results showed that the wife’s right to her husband was the right to get good treatment, get teachings from the husband, get protection from the husband, and get proper food and clothing. While the wife’s obligation to her husband is to obey his orders as long as he does not violate God’s rules, safeguarding the husband’s wealth, respecting the husband’s family, and dressing to look beautiful according to the husband